Low-voltage-activated A-current controls the firing dynamics of mouse hypothalamic orexin neurons - Burdakov, Denis (Eur J Neurosci, 2004)
The activity of hypothalamic neurons that release the neuropeptides orexin-A and orexin-B is essential for normal wakefulness. Orexin neurons fire spontaneously and are hyperpolarized and inhibited by physiological neuromodulators, but the intrinsic determinants of their electrical activity are poorly understood. We show that mouse orexin neurons coexpress orexin-A and orexin-B, and possess a low-voltage-activated A-type K(+) current (A-current) likely to be composed of Kv4.3 subunits. The A-current enhances the inhibitory influence of hyperpolarizing currents via two mechanisms: by delaying the resumption of spiking after hyperpolarization and by increasing the slope of the relation between the firing frequency and injected current. These results identify an important determinant of the firing dynamics of orexin neurons, and support the idea that the A-current can control neuronal gain.